Gene2Function: An Integrated Online Resource for Gene Function Discovery - Yanhui Hu; Aram Comjean; Stephanie E. Mohr; The FlyBase Consortium; Norbert Perrimon (G3: Genes, Genomes, Genetics, 2017)
One of the most powerful ways to develop hypotheses regarding the biological functions of conserved genes in a given species, such as humans, is to first look at what is known about their function in another species. Model organism databases and other resources are rich with functional information but difficult to mine. Gene2Function addresses a broad need by integrating information about conserved genes in a single online resource.